In Guatemala, They Stripped Us the Right to Life, but also the Right to Die. Forty-five Thousand Persons Dissapeared and Detained by the State of Terror - Fuentes-Rosales, Alberto (2017)
This text presents an analysis of the systematic terror of State put in practice in Guatemala against its population through kidnapping, disappearance and forced detention, and the processes the Archivo Histórico (Historical Archives) is leading in the country to exhume, identify and denounce these genocide facts.